Fist of the North Star. Volume 3 - Buronson, 1947- (Viz signature., 2021)
"Ken's mastery of Hokuto Shinken, the Divine Fist of the North Star, has no equal among the debased gangs that prey on the ruins of civilization. But Ken is not the only martial artist out there. Rei, a user of the Nanto Suichoken technique, is on a journey to find his sister, who is being held by a brutal band of savages known as the Fangs. Ken and Rei team up to find her, and woe to any who stand in their way!"--Back cover